Discovering microbiota and volatile compounds of surströmming, the traditional Swedish sour herring. (October 2020) - Belleggia, Luca; Aquilanti, Lucia; Ferrocino, Ilario; Milanović, Vesna; Garofalo, Cristiana; Clementi, Francesca; Cocolin, Luca; Mozzon, Massimo; Foligni, Roberta; Haouet, M. Naceur; Scuota, Stefania; Framboas, Marisa; et al.
Abstract: In this study, the microbiota of ready-to-eat surströmming from three Swedish producers were studied using a combined approach. The pH values of the samples ranged between 6.67 ± 0.01 and 6.98 ± 0.01, whereas their aw values were between 0.911 ± 0.001 and 0.940 ± 0.001. The acetic acid concentration was between 0.289 ± 0.009 g/100 g and 0.556 ± 0.036 g/100 g. Very low concentrations of lactic acid were measured. Viable counting revealed the presence of mesophilic aerobes, mesophilic lactobacilli and lactococci as well as halophilic lactobacilli and lactococci, coagulase-negative staphylococci, halophilic aerobes and anaerobes. Negligible counts for Enterobacteriaceae, Pseudomonadaceae and total eumycetes were observed, whereas no sulfite-reducing anaerobes were detected. Listeria monocytogenes and Salmonella spp. were absent in all samples. Multiplex real-time PCR revealed the absence of the bont/A, bont/B, bont/E, bont/F, and 4gyrB (CP ) genes, which encode botulinic toxins, in all the samples analyzed. Metagenomic sequencing revealed the presence of a core microbiota dominated by Halanaerobium praevalens, Alkalibacterium gilvum, Carnobacterium spp., Tetragenococcus halophilus, Clostridiisalibacter spp. and Porphyromonadaceae . Psychrobacter celer, Ruminococcaceae, Marinilactibacillus psychrotolerans, Streptococcus infantis and Salinivibrio costicola were detected as minor OTUs. GC-MS analysis of volatile components revealed the massive presence of trimethylamine and sulphur compounds. Moreover, 1, 2, 4-trithiolane, phenols, ketones, aldehydes, alcohols, esters and long chain aliphatic hydrocarbons were also detected. The data obtained allowed pro-technological bacteria, which are well-adapted to saline environments, to be discovered for the first time. Further analyses are needed to better clarify the extent of the contribution of either the microbiota or autolytic enzymes of the fish flesh in the aroma definition. Highlights: The microbiota of surströmming samples from three Swedish producers was studied. Alkalibacterium, Carnobacterium and Tetragenococcus were detected in all the samples. Halanaerobium, Clostridiisalibacter and Porphyromonadaceae were also found. Listeria monocytogenes, Salmonella and botulinic toxins genes were never detected. The massive presence of trimethylamine and sulphur compounds was detected.